The Tirrell regulator - Wilson, J. A.; Strong, H. D. (My University, 1908)
Introduction: The voltage regulation of electrical generators has always been a very important problem, and one that has been very difficult to solve. Formerly when the field was held by shunt generators the supply depended entirely upon a switch board attendant who endeavored to keep the voltage as nearly as possible to the desired point…
Citation: Wilson, J. A. and Strong, H. D. The Tirrell regulator. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Regulators; Electricity; Tirrell; Generators; Graduating theses; Senior theses; Theses